2019
DOI: 10.1007/s00300-019-02587-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes and consistencies in marine and coastal bird numbers on Kidney Island (Falkland Islands) over half a century

Abstract: Detecting change is necessary for effective ecosystem management, yet temporal data on key ecosystem components are lacking for many polar and subpolar regions. For example, although the Falkland Islands hosts internationally important marine and coastal bird populations, few of these were surveyed until the late 20th century. The avifauna of one small island, Kidney Island, was surveyed between 1958 and 1963, however. This typical tussaccovered island has remained free of non-native predators, so changes in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Specific to the species in this study, high breeding site fidelity has been observed for the same or related species such as the sea ducks (Mallory, 2015), penguins (Williams & Rodwell, 1992), gulls (Stenhouse & Robertson, 2005), cormorants (Sapoznikow & Quintana, 2008), shearwaters (Sugawa et al, 2014), albatrosses and petrels (Bried et al, 2003). At the Falkland Islands, many seabird breeding sites have remained predictable over time (Catry et al, 2019; Crofts & Stanworth, 2019). Consequently, the areas we identified as globally important are expected to be stable across years, further benefitting confidence in the use of these sites as a key input for marine spatial planning efforts by decision‐makers.…”
Section: Discussionmentioning
confidence: 99%
“…Specific to the species in this study, high breeding site fidelity has been observed for the same or related species such as the sea ducks (Mallory, 2015), penguins (Williams & Rodwell, 1992), gulls (Stenhouse & Robertson, 2005), cormorants (Sapoznikow & Quintana, 2008), shearwaters (Sugawa et al, 2014), albatrosses and petrels (Bried et al, 2003). At the Falkland Islands, many seabird breeding sites have remained predictable over time (Catry et al, 2019; Crofts & Stanworth, 2019). Consequently, the areas we identified as globally important are expected to be stable across years, further benefitting confidence in the use of these sites as a key input for marine spatial planning efforts by decision‐makers.…”
Section: Discussionmentioning
confidence: 99%